2015
DOI: 10.1002/etc.3055
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of graphene oxide by ferrous iron: Environmental implications

Abstract: Abiotic transformation of graphene oxide (GO) in aquatic environments can markedly affect the fate, transport, and effects of GO. The authors observed that ferrous iron (Fe[II])-an environmentally abundant, mild reductant-can significantly affect the physicochemical properties of GO (examined by treating aqueous GO suspensions with Fe(2+) at room temperature, with doses of 0.032 mM Fe(2+)  per mg/L, 0.08 mM Fe(2+)  per mg/L, and 0.32 mM Fe(2+)  per mg/L GO). Microscopy data showed stacking of GO nanosheets on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…These observations indicate that the pCNPs discussed above may be more prone to transformation than eCNPs as they generally contain Environmental Science: Nano Critical review smaller aromatic sheets, as well as more structural irregularities and mineral phases. 28,50 Chemical transformation of pCNPs can be influenced by environmental factors such as light, 15,16,51 or the presence of oxidants (e.g., O 2 ), 15 reductants (e.g., Fe 2+ and S 2− ), 6,[52][53][54] and natural organic matter (NOM). 55,56 The factors driving chemical transformation differ markedly between (i) soot, which is mainly transported via the atmosphere and more susceptible to photochemical reactions involving reactive oxygen species (ROS), and (ii) other pCNPs, which are mainly transported by surface runoff and subsurface infiltration, where redox reactions with O 2 or S 2− are likely to be more important.…”
Section: Chemical Transformationmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations indicate that the pCNPs discussed above may be more prone to transformation than eCNPs as they generally contain Environmental Science: Nano Critical review smaller aromatic sheets, as well as more structural irregularities and mineral phases. 28,50 Chemical transformation of pCNPs can be influenced by environmental factors such as light, 15,16,51 or the presence of oxidants (e.g., O 2 ), 15 reductants (e.g., Fe 2+ and S 2− ), 6,[52][53][54] and natural organic matter (NOM). 55,56 The factors driving chemical transformation differ markedly between (i) soot, which is mainly transported via the atmosphere and more susceptible to photochemical reactions involving reactive oxygen species (ROS), and (ii) other pCNPs, which are mainly transported by surface runoff and subsurface infiltration, where redox reactions with O 2 or S 2− are likely to be more important.…”
Section: Chemical Transformationmentioning
confidence: 99%
“…For example, GO can be transformed in aquatic environments because of its abundant surface O-functional groups, while Fe 2+ and S 2− can reduce GO thereby increasing its hydrophobicity. 6,52,54 However, Wang et al 53 found that GO reduction by Fe 2+ resulted in a reduced content of alkoxy and hydroxy groups and an increased content of carboxy groups because of the hydrolysis reaction of acid anhydrides on GO. Chemical reduction can therefore also result in the formation of polar surface groups and the effect of redox reactions needs to be evaluated on a case-by-case basis.…”
Section: Chemical Transformationmentioning
confidence: 99%
“…This fact, along with the ability of some bacteria [33] and naturally occurring organics [34], sulfides [35] and ferrous iron [36] to reduce GO as well, indicates that the majority of GO released to the environment could became RGO after certain time. In this regard, Chowdhury et al [37] used the quartz crystal microbalance with dissipation monitoring to analyse the deposition and release onto silica and NOM-coated silica surfaces of GO aerobically photoreduced for 1, 3, 11, 61 and 187 hours, and anaerobically photoreduced for 3, 11 and 61 hours.…”
Section: Piping and Pretreatmentmentioning
confidence: 96%
“…So, by extrapolation, it can be inferred that, if there were low amounts of GO bound to the coarse solids and to the sand, there will be less RGO. However, due to the hydrophobicity of the reduced species, they could agglomerate through van der Waals forces more readily than GO, and a fraction of them could settle in the grit chamber, since, in some cases, sedimentation in deionised water after reduction took place in minutes [36]. Notwithstanding the foregoing, according to Chowdhury et al [37], NOM improves the stability of deionised water + electrolyte + RGO, and keeping in mind the relatively high amount of organic matter contained in the sewage, the reduced nanomaterial settled down together with the grit will be little if adsorption on other minerals than sand is not very strong (to the best of our knowledge, there are not studies similar to those of GO with kaolin/kaolinite, hematite, montmorillonite, goethite and layered double hydroxides for RGO).…”
Section: Piping and Pretreatmentmentioning
confidence: 98%
“…[53] For example, ferrous ions (Fe 2+ ) can reduce graphene oxide. [54] In an aerated soil with high oxygen content, oxidation of ENMs is more favorable. This may result in the formation of an oxide layer on the surface of some metallic ENMs which can act as a protective coating for the particle core.…”
Section: Drivers Of Enms Transformation In Soilmentioning
confidence: 99%